2021
DOI: 10.1111/jace.17769
|View full text |Cite
|
Sign up to set email alerts
|

Phase content prediction in polymer‐derived ceramics with metal additives

Abstract: Recently, polymer-derived ceramics (PDCs) have raised great interest due to a series of advantages over other traditional ceramics, such as chemical, thermal, and oxidation stabilities. [1][2][3] PDCs can be divided into different categories: binary (e.g., SiC), ternary (e.g., SiCN, SiOC), or quaternary systems (e.g., SiOBC). 4 SiOC can be described as a nanosystem composed of SiO x C 4x units with dispersed turbostratic carbon, SiO 2 , or SiO 2 plus SiC 2,5-7 and exhibits remarkable application potentials in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Our 4D scanning TEM work attempted to distinguish the phase distribution of SiOC systems, but the information is for a specific pyrolyzed state 1 . On the theoretical side, we have developed a Gibbs energy minimization approach to calculate the percentages of different amorphous phases 2–4 . Still, the exact thermodynamic process is unknown and the calculated phase amounts cannot be verified.…”
Section: Figurementioning
confidence: 99%
“…Our 4D scanning TEM work attempted to distinguish the phase distribution of SiOC systems, but the information is for a specific pyrolyzed state 1 . On the theoretical side, we have developed a Gibbs energy minimization approach to calculate the percentages of different amorphous phases 2–4 . Still, the exact thermodynamic process is unknown and the calculated phase amounts cannot be verified.…”
Section: Figurementioning
confidence: 99%
“…13 At even higher temperatures (usually >1100 • C), the additional formation of Fe 3 Si was recorded. 14,15 It is assumed that the detected Si 2 N 2 O phase (Figure 5) is formed via the vapor-liquid-solid (VLS) process. 19…”
Section: Rietveld Refinementmentioning
confidence: 99%
“…11,12 It was furthermore shown that the metal (M)-containing polymer-derived ceramic systems Si-M-O-C, Si-M-C, or Si-M-C-N-O are thermodynamically controlled regarding their partitioning and crystallization behavior at elevated temperatures. 13,14 Consequently, the phase composition and microstructure can be predicted and thus tailored accordingly. For instance, extensive studies showed that metal-containing Si-O-C systems provide preparative access to ceramic nanocomposites consisting of a SiOC matrix and incorporating metal oxide secondary phases (as for early transition metals, e.g., belonging to group IV), metal carbides (as for groups V and VI transition metal), pure metals (e.g., Sn, Ni), metal silicides (e.g., Fe, Co, Pd) or metal silicates (e.g., alkaline or earth alkaline metals) as nanostructured precipitates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Substantial work with the prospects of understanding decomposition mechanisms, phase/microstructure evolution, and properties/performance of PDCs modified with transition metals was investigated over the past decade. [9][10][11][12][13][14] Combining PDCs with intermetallic or metallic nanoparticles (NPs) on the molecular level before pyrolysis can extend the applications in catalytic and other areas. For example, García et al [15] reported that the novel Ce/SiOC composite via the polymer-derived route performed porous thermocatalysts, which produced the maximum amount of CO gas at 1200-1300 °C.…”
Section: Introductionmentioning
confidence: 99%